Staying Online : how to navigate digital higher education - Ubell, Robert (Vice dean of online learning) (New York, NY : Routledge, 2022)
"In Staying Online, one of our most respected online learning leaders offers uncommon insights into how to reimagine digital higher education. As colleges and universities increasingly recognize that online learning is central to the future of post-secondary education, faculty and senior leaders must now grapple with how to assimilate, manage, and grow effective programs. Looking deeply into the dynamics of online learning today, Robert Ubell maps its potential to boost marginalized students, stabilize shifts in retention and tuition, and balance nonprofit and commercial services. This impressive collection spans the author's day-to-day experiences as a digital learning pioneer, presents pragmatic yet forward-thinking solutions on scaling-up and digital economics, and prepares managers, administrators, provosts, and other leaders to educate our unsettled college students as online platforms fully integrate into the mainstream"--
Includes bibliographical references and index.
Keywords: Internet in higher education; Web-based instruction